Is endoscopy mandatory in cases mimicking acute pancreatitis? - Mohammed Hussien Ahmed,; Mohammed Said Radwan,; Amira Amin Salem Tawoos3,; Rasha Ibrahim Salama, (Journal of the Pakistan Medical Association, 2023)
N/A